Purchase Intention Model of Generation Z to Enhance Awareness of Green Products Consumptions - Sari, Shinta Permata; Witono, Banu; Fatwasari Soeratno Putri; Gehad Mohammed Sultan Saif (Riset Akuntansi dan Keuangan Indonesia, 2024)
The increased world population makes the carrying capacity of nature even heavier and leads to various environmental problems. Consumption of green products is one of the solutions to overcome environmental problems. Based on previous research, people still perceive green products as having lower quality with higher prices than conventional products, so it becomes a barrier for companies or industries to identify how to develop marketing strategies for green products. This study aims to determine how consumers, especially Generation Z in Indonesia, construct green purchase intention by examining the impact of consumption value, the mediating effect of utility, and the moderating effect of price-related judgment (materialism and value consciousness). There are 266 Indonesian Generation Z used as respondents in this study. This study is analyzed by using Smart PLS 4.0 application. The results show that functional value, social value, and experiential value positively and significantly affect acquisition utility and transaction utility, acquisition utility positively and significantly affect transaction utility, acquisition utility and transaction utility positively and significantly affect green purchase intention, materialism orientation does not moderate functional value and experiential value on transaction utility, value consciousness moderates social value on transaction utility, and value consciousness does not moderate functional value and experiential value on transaction utility.